Respuesta :

Answer:

The mistake is that the equation on both sides is multiplied by 8. Both sides should be divided by 8.

Step-by-step explanation:

[tex]8x^2-x-1=0[/tex]
[tex]8x^2-x=1[/tex]   Divide both sides of the equation by 8
[tex]x^2-\frac{1}{8} x=\frac{1}{8}[/tex]
[tex]x^2-\frac{1}{8} x+?=\frac{1}{8} +?[/tex] Add the same value to both side
[tex]x^2-\frac{1}{8} x+\frac{1}{256} =\frac{1}{8} +\frac{1}{256}[/tex]              
Use [tex]a^2-2ab+b^2=(a-b)^2[/tex]
[tex](x-\frac{1}{16} )^2 = \frac{33}{256}[/tex]
[tex]x-\frac{1}{16}=+-\frac{\sqrt{33} }{16}[/tex]
[tex]x_{1} =\frac{-\sqrt{33}+1 }{16}[/tex]
[tex]x_{2} =\frac{\sqrt{33}+1 }{16}[/tex]


Answer:

[tex]x=\dfrac{1 \pm \sqrt{33}}{16}[/tex]

Step-by-step explanation:

Given:

[tex]8x^2-x-1=0[/tex]

Add 1 to both sides:

[tex]\implies 8x^2-x=1[/tex]

Factor out the 8 from the left side:

[tex]\implies 8\left(x^2-\dfrac{1}{8}x\right)=1[/tex]

Divide both sides by 8:

[tex]\implies x^2-\dfrac{1}{8}x=\dfrac{1}{8}[/tex]

Add the square of half the coefficient of x to both sides:

[tex]\implies x^2-\dfrac{1}{8}x+\dfrac{1}{256}=\dfrac{1}{8}+\dfrac{1}{256}[/tex]

Factor the left side and simplifyy the right:

[tex]\implies \left(x-\dfrac{1}{16}\right)^2=\dfrac{33}{256}[/tex]

Square root both sides:

[tex]\implies x-\dfrac{1}{16}=\pm\sqrt{\dfrac{33}{256}}[/tex]

Simplify:

[tex]\implies x-\dfrac{1}{16}=\pm\dfrac{\sqrt{33}}{16}[/tex]

Add 1/16 to both sides:

[tex]\implies x=\pm\dfrac{\sqrt{33}}{16}+\dfrac{1}{16}[/tex]

Simplify:

[tex]\implies x=\dfrac{1 \pm \sqrt{33}}{16}[/tex]

ACCESS MORE